Russian Cultural Policy: Goals, Threats, and Solutions in the Context of National Security - Efremova, Lyudmila Anatolyevna; Rusetskiy, Mikhail Gennad’evich; Molchan, Alexey Sergeevich; Lechman, Elena Vladimirovna; Avdeeva, Rosa Aleksandrovna (Journal of History Culture and Art Research, 2018)
The developed countries of the mid-XX century acknowledge the importance of the effective use of intellectual resources for providing sustained social development. The implementation of the formation principles of democratic information society and Russia’s desire to integrate into the world community contributed to the conscious need of transiting from the paternalistic concept of cultural policy to the partnership concept, which is innovative in many ways. It should be noted that a number of significant strategic planning documents that determine a high status of culture as a national Russian priority appeared in 2008-2017. Thus, state cultural policy requires clear goals, principles and tasks, on the one hand, and the awareness of possible threats, on the other hand. The elements of scientific novelty are determined by the fact that the article justifies the necessity to understand the modern approaches towards the development and implementation of state cultural policy in the Russian Federation. At the same time, it is noted that the concept and strategy of cultural policy should take into account both the acknowledged political ideology and the issues of financial support of the cultural sphere.